Bulk polymerization of vinyl pivalate using low-temperature azoinitiator and saponification for the preparation of poly(vinyl alcohol) microfibrils - Lyoo, WS; Han, SS; Kim, JH; Yoon, WS; Lee, CJ; Kwon, IC; Lee, J; Ji, BC; Han, MH (WILEY-V C H VERLAG GMBH, 1999)
Vinyl pivalate (VPi) was bulk-polymerized at 30, 40, and 50 degrees C using a low temperature initiator, i.e. 2,2'-azobis(2,4-dimethylvaleronitrile) (ADMVN). The effects of polymerization temperature and initiator concentration were investigated in terms of polymerization behavior and molecular structures of poly(vinyl pivalate) (PVPi) and corresponding poly(vinyl alcohol) (PVB) microfibrillar fiber obtained by saponification in KOH/methanol/water, Low polymerization temperature using ADMVN proved to be successful in obtaining PVA of syndiotacticity-rich high molecular weight. PVPi had a number-average degree of polymerization (P-n) of 27 100-35 900, and a degree of branching for pivaloyl group of 0.8-1.0 at 30 degrees C, 1.0-1.3 at 40 degrees C, and 1.4-1.7 at 50 degrees C at conversions below 40%. Saponification of PVPi yielded PVA having a P-n of 10 400-16 500, and syndiotactic diad (S-diad) content of 58.8-61.5%. It was found that all PVA specimens represented microfibrillar morphologies, with high crystallinity and orientation. The S-diad content and crystal melting temperature were higher with PVA prepared from PVPi polymerized at lower temperatures.
Keywords: SUSPENSION POLYMERIZATION; ACETATE; POLYVINYLALCOHOL